Asymptomatic Pseudotumors in Patients with Taper Corrosion of a Dual-Taper Modular Femoral Stem: MARS-MRI and Metal Ion Study. (19th October 2016) - Kwon, Young-Min; Khormaee, Sariah; Liow, Ming Han Lincoln; Tsai, Tsung-Yuan; Freiberg, Andrew A.; Rubash, Harry E.
Abstract : Background: Modularity in total hip arthroplasty facilitates intraoperative restoration of patient anatomy. Although dual-taper modular total hip arthroplasty offers potential advantages for optimizing the hip center of rotation, it has been associated with modular taper corrosion. This corrosion has led to adverse local tissue reactions (pseudotumors) at the neck-stem junction and elevated metal-ion levels. However, the occurrence of taper-corrosion-related pseudotumors in patients who remain asymptomatic following total hip arthroplasty with a dual-taper modular femoral stem remains largely unknown. The aims of this study were (1) to determine the prevalence of asymptomatic pseudotumors by utilizing metal artifact reduction sequence magnetic resonance imaging (MARS-MRI) and (2) compare serum metal-ion levels between symptomatic and asymptomatic patients with a dual-taper modular stem total hip replacement. Methods: We performed a retrospective cross-sectional study of 97 consecutive patients who had been treated with a dual-taper modular femoral stem total hip arthroplasty. Eighty-three patients were stratified into symptomatic and asymptomatic groups and evaluated with MARS-MRI, measurement of serum metal-ion levels, and the University of California at Los Angeles (UCLA) functional hip score. Results: The prevalence of pseudotumors as determined with MARS-MRI was 15% in our asymptomatic patients and 36% in the overall cohort. The median serum cobalt level and cobalt/chromium ratio were significantly higher in patients with a pseudotumor than in those without a pseudotumor (8.0 versus 2.0 μg/L [p = 0.004] and 10.3 versus 2.4 μg/L [p = 0.012], respectively). However, there was no significant difference in the serum cobalt level or cobalt/chromium ratio between symptomatic patients with a pseudotumor and asymptomatic patients with a pseudotumor (7.6 versus 6.2 μg/L [p = 0.37] and 8.3 versus 10.6 μg/L [p = 0.46], respectively). The UCLA scores of asymptomatic patients with a pseudotumor were similar to those of patients without a pseudotumor (6.7 versus 6.6). Conclusions: The prevalence of asymptomatic taper-corrosion-related pseudotumors on MARS-MRI in this study demonstrated that the absence of symptoms does not exclude the presence of adverse local tissue reactions. Elevated cobalt levels and cobalt/chromium ratios were associated with the presence of pseudotumors in asymptomatic and symptomatic patients. Cross-sectional imaging such as MARS-MRI is indicated for patients with elevated metal-ion levels. A longitudinal study is required to determine whether asymptomatic patients with taper-corrosion-related pseudotumors will develop symptoms with time. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.